PLAY PERFORMANCE SUBJECT FOR NON-LITERARY STUDENTS: CHALLENGES AND STRATEGY - Subanti, Gregorius (Prologue: Journal on Language and Literature, 2024)
Mastering English language skills can be quite challenging for students in any levels, including college students. To answer the existing problem, there are many introduced techniques in building students’ language skills. One of the techniques of learning is using role play or play performance. This study aims at investigating students’ perception of Play Performance, as a subject taught in semester four, in improving their language skills namely Speaking, Reading, Listening and Writing. This study uses qualitative approach which requires students to fill out the written open interview of how they perceive the subject. The findings are positive. Majority of students respond that Play Performance subject help them improve reading, listening, writing and speaking skills significantly. The improvement boosts their confidence in using English in their academic activities